2019
DOI: 10.1002/adma.201900613
|View full text |Cite
|
Sign up to set email alerts
|

Multiphotoluminescence from a Triphenylamine Derivative and Its Application in White Organic Light‐Emitting Diodes Based on a Single Emissive Layer

Abstract: White organic light‐emitting diode (WOLED) technology has attracted considerable attention because of its potential use as a next‐generation solid‐state lighting source. However, most of the reported WOLEDs that employ the combination of multi‐emissive materials to generate white emission may suffer from color instability, high material cost, and a complex fabrication procedure which can be diminished by the single‐emitter‐based WOLED. Herein, a color‐tunable material, tris(4‐(phenylethynyl)phenyl)amine (TPEPA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 31 publications
0
27
0
Order By: Relevance
“…Most importantly, due to the lack of efficient and stable deep blue emitters, the general characteristic of voltage‐dependent CIE chromaticity coordinates in multilayered WOLEDs would result in an unstable emission color of the devices . Therefore, a single‐molecular system, which is white‐light emissive, would be an ideal material to develop a highly efficient WOLED with less phase separation, more simple device structure and stable emission color . To date, there are some review articles on the white‐light generation from a single phase, in which multifunctional molecules are used to assemble the white‐light emissive supramolecules or nanostructures .…”
Section: Introductionmentioning
confidence: 99%
“…Most importantly, due to the lack of efficient and stable deep blue emitters, the general characteristic of voltage‐dependent CIE chromaticity coordinates in multilayered WOLEDs would result in an unstable emission color of the devices . Therefore, a single‐molecular system, which is white‐light emissive, would be an ideal material to develop a highly efficient WOLED with less phase separation, more simple device structure and stable emission color . To date, there are some review articles on the white‐light generation from a single phase, in which multifunctional molecules are used to assemble the white‐light emissive supramolecules or nanostructures .…”
Section: Introductionmentioning
confidence: 99%
“…However, these accumulated holes can form polarons and can quench excitons via excitonpolaron annihilation leading to decreased efficiency and operation lifetime [15][16][17][18][19][20][21][22][23][24] . It can be seen that in either scenario, both efficiency and operation lifetime are harmfully affected.…”
mentioning
confidence: 99%
“…4 . For example, in some organic molecules 16 , 38 such as triphenylamine derivatives, thermally activated rotation in the molecular structure leads to the enhancement of π–π stacking and electronic coupling, which thereby results in a redshift in some molecules. In some crystals, the lattice distortion-induced self-trapping state can also promote the coexistence of multicolour centres and has attracted much attention for some perovskite emitters in recent years, such as Cs 2 Ag 0.60 Na 0.40 InCl 6 , δ -CsPbI 3 , and CsCu 2 I 3 26 , 28 , 29 .…”
Section: Emitters and Their Electroluminescence Mechanism In Wledsmentioning
confidence: 99%
“…Li, X. et al reported a small molecule, tris(4-(phenylethynyl)phenyl) amine (TPEPA), with the characteristic adjustable photoluminescence (PL) spectrum covering almost the entire visible-light band, which was controlled by annealing temperature (Fig. 6d ) 16 . When the annealing temperature is reached, the benzene ring and bis(phenylethylnyl)benzene in the organic molecular structure rotate, which changes the energy level and forms different species that emit blue, green, and red colours (Fig.…”
Section: Cases Of Wleds With a Single Emissive Layermentioning
confidence: 99%
See 1 more Smart Citation